2017
DOI: 10.1002/cepa.253
|View full text |Cite
|
Sign up to set email alerts
|

08.30: Experimental investigation and specific behaviour of X‐HVB shear connectors in prefabricated composite decks

Abstract: Construction industry is constantly facing new demands towards fast construction and smallest possibly quantity of work at the construction site. These increasing demands, in the field of composite construction of buildings and bridges, resulted in development of different types of prefabricated composite decks during decades and group arrangement of different types of shear connectors. Positioning of shear connectors into envisaged openings of prefabricated composite decks contributes to smaller quantity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The shear connecter (X-HVB) is an L-shaped shear connector that comes in various heights (from 40 to 140 mm). Hilti DX 76 or DX 76 PTR powder-actuated tools and Hilti DX cartridge equipment were used to attach two XENP-21 HVB nails to the composite constructions with or without profiled steel sheeting [13]; Fig. 2 depicts all of these components.…”
Section: Hilti X-hvb Shear Connectormentioning
confidence: 99%
See 1 more Smart Citation
“…The shear connecter (X-HVB) is an L-shaped shear connector that comes in various heights (from 40 to 140 mm). Hilti DX 76 or DX 76 PTR powder-actuated tools and Hilti DX cartridge equipment were used to attach two XENP-21 HVB nails to the composite constructions with or without profiled steel sheeting [13]; Fig. 2 depicts all of these components.…”
Section: Hilti X-hvb Shear Connectormentioning
confidence: 99%
“…(a) X-HVB shear connector with two X-ENP-21 HVB nails [15] (b) DX 76 PTR tool, equipped for X-HVB installation [16] (c) cartridges [16] Fig. 2: Hilti X-HVB System.…”
Section: Hilti X-hvb Shear Connectormentioning
confidence: 99%
“…Pull-out, coming together with tilting of fasteners, is also characteristic of shear connectors fastened to the steel base material with the same cartridge fired pins and placed in solid or composite concrete slabs [4,5,12]. The average shear force per one fastener, when they are applied for utilization of shear connection with X-HVB shear connectors in solid concrete slabs, is between 17.79 kN and 20.96 kN.…”
Section: Shear Testsmentioning
confidence: 99%
“…The average shear force per one fastener, when they are applied for utilization of shear connection with X-HVB shear connectors in solid concrete slabs, is between 17.79 kN and 20.96 kN. The shear force range is captured for various specimen layouts [5,12] and energy driven through fastening. The lower value of shear force is achieved for specimens where fasteners were installed with the settlement of 2.0 power level on the power regulation device, while higher force is obtained for 3.5 power level, which is the same value used for installation of shear test specimens -ST.…”
Section: Shear Testsmentioning
confidence: 99%
“…X-HVB shear connectors prevent vertical uplift forces by using the X-HVB head and nails and are designed to resist desired shear forces with suitable ductility (Hilti X-HVB System [94]). Gluhović et al [95] tested the prefabricated composite deck by conducting push-out tests pursuant to Eurocode 4 [10] to assess the shear capacity of X-HVB connectors with powder-actuated fastener X-ENP-21 HVB nails. Their results showed that 26% higher slip to failure and 16% higher ultimate shear resistance to forward orientated shear connectors.…”
Section: Hilti X-hvb Shear Connectorsmentioning
confidence: 99%